ENHANCEMENT THE EFFECTIVENESS OF GOVERNMENT COMMUNICATIONS IN INFOGRAPHIC IMMIGRATIONS THROUGH SOCIAL MEDIA PLATFORM - Riyan Herriandi Putra (Polteknik Imigrasi, 2020)
The infographic content published by the Immigration Technical Service Unit is considered to have not maximized regarding the use of design elements referring to Visual Communication Design Theory. This is due to the lack of the public relations staff’s knowledge of the theory and their educational background that are not related to communication design. The purposes of this research are to know the quality of government communication through infographic media and the importance of infographic media as a means to spread information, especially immigration information as well as this study has the impact of proposing standardization on the infographics published by each technical service unit under the Directorate General of Immigration. In this study, the authors used a qualitative approach with descriptive methods by collecting data through interviewing techniques for respondents and observations made in a comprehensive manner. in the network to get credible data. The results of this study are proven that the use of design elements in Visual Communication Design Theory has not been maximal in the place where the author conducted the research. Therefore the authors provide a recommendation for the existence of guidelines that contain standardization of infographic layout designs that will equalize all design elements for use by designers in each Immigration Technical Service Unit. In addition, to improve image and positive public perceptions of each Immigration Technical Service Unit as well as increase public confidence in in an information that published by each Immigration Technical Service Unit.